Social and ethical issues in design and technology - Baricevic, Thomas; Boland, Michael; Video Education Australasia (Australia : Video Education Australasia, 2007)
This program explores the associated social, lifestyle, ethical and ecological considerations that designers and multinational companies must address while moving through the design cycle
Title from title screen
Executive producer, Mark McAuliffe ; senior producer, Richard Leigh ; editor, Thomas Baricevic ; camera, Peter Zakharov, Peter Andrian
Voice over: Amanda Brocklebank
DVD Format
Keywords: Industrial design; Design; Technology; Social ethics